INNOVATIONS TO MAXIMISE THE REACH OF INTEGRATED MATERNAL AND CHILD HEALTH SERVICES IN REDUCING MATERNAL AND INFANT MORTALITY RATES AT DAYA GENERAL HOSPITAL MAKASSAR - Husnul Khatimah Fachmi; Novayanti Sopia Rukmana; Herlina Sakawati (Universitas Negeri Makassar, 2026)
The high MMR and IMR are a problem in health services at Daya Regional Hospital, Makassar City. This research aims to determine the implementation of the Maximum Reach Innovation for Integrated Maternal and Child Health Services in Reducing MMR and IMR in the Daya Hospital of Makassar City. This research uses a qualitative approach with a descriptive method with data collection techniques in this research namely interviews, observation and documentation. Checking the validity of the data in this research was carried out by source triangulation. Data analysis techniques use data condensation, data presentation and drawing conclusions. The results of this research show that the implementation of innovation for maximum coverage of integrated maternal and child health services is based on Stephen Robbins' theoretical indicators, namely having distinctive/special characteristics, having characteristics or elements of novelty, the innovation being rolled out has the aim of having been implemented well. However, the indicators of innovation programs implemented through planned programs still require some improvement in order to provide quality services for pregnant and giving birth mothers. This innovation needs to maintain its existence, especially ensuring that this program continues to run so that the goals to be achieved in creating innovations for maximum coverage of integrated maternal and child health services can reduce MMR and IMR maximally.